EVALUATION OF ISLAMIC RELIGIOUS EDUCATION BASED ON LEARNING MANAGEMENT SYSTEM - Mundir Mundir (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This research focuses on the process of understanding the stages of evaluating Islamic Religious Education (PAI) learning at SMA Negeri 2 Jember through the Learning Management System platform. This study aims to analyze the design of digital-based PAI learning evaluations through LMS organized by SMAN 2. This research uses a qualitative approach to produce descriptive data in observable behavior, written data, and oral data. At the same time, data analysis is carried out through the interactive technique of Miles, Hubermann, and Saldana. The conclusion of this research states that the design of PAI learning evaluation through the use of LMS at SMA Negeri 2 Jember uses a blended evaluation design that integrates the LMS Moodle (Attendance register; Assignment; Chat; Feedback; Database activity) and evaluation through mutaba'ah sheets. This composite evaluation design ultimately leads to the achievement of students' cognitive, affective, and psychomotor competencies but remains adaptive to the demands of educational innovation in the current COVID-19 pandemic. Therefore, the application of LMS as an online learning platform in the era of the COVID-19 pandemic has an urgent position to be studied and analyzed in depth.